ANALISIS TINGKAT KEBISINGAN DI UNIVERSITAS SEMARANG DENGAN PETA KONTUR MENGGUNAKAN SOFTWARE GOLDEN 1 - Ahmad, Fahrudin; Dwi Handayani, Iryan; Margiantono, Agus (Elektrika, 2018)
Campus is a place which is teaching and learning process occur. One factor that support a good learning environment is to avoid noise problems. The object of the research is the campus of Semarang University located on Jalan Arteri Soekarno-Hatta, it is located on the edge of the Kaligawe-Gayamsari toll road. Both roads includes the most crowded transportation routes in Semarang City.Campus area requires a quiet and silent environment. It is difficult for the urban areas to get a quiet campus environment. The study tries to reveal the evaluation on how the noise factors that occur during teaching and learning process. The study was conducted at Semarang University. The research method used is descriptive analytic method. The research was conducted by measuring the noise level using Sound Level Meter (KRISBOW) type KW08-291, several data collection points was taken at Semarang University, both open and closed environments around campus. The results of noise measurements would be carried out in noise mapping to know the noise distribution map in the campus area. The noise level in the campus is still above 55 dB on average. It shows that the noise level in the environment of Semarang University has not been in line with the predetermined standard that is still greater than (40 - 50 dBA) in accordance to the decree of the State Minister of the Environment number 48 of 1996.Keywords: noise, sound level meter, noise threshold value, decree of the State Minister of the Environment number 48 of 1996